Edukasi Pemilu 2024 Berbasis Multiliterasi Untuk Pemilih Pemula Di SMAN 02 Minas - Rianita, Dian; Yandra, Alexsander; Husna, Khuriyatul; Amelia, Vita; Suratmi, Suratmi (UNIVERSITAS MUHAMMADIYAH MATARAM, 2024)
The 2024 General Election is a very important democratic party for the people of Indonesia. Higher political awareness is a must for every level of society, especially for the increasing number of potential first-time voters. The fact that prospective first-time voters in the 2024 elections are mostly from the Milleneal Generation and Generation Z, this community service activity is very important. Based on this consideration, this community service PKM) was carried out at SMAN 02 Minas as the initial location of a series of multiliteracy-based political education activities with the aim of providing knowledge and increasing the understanding of students at SMAN 02 Minas as prospective participants in the 2024 elections. The result of this activity is the increased knowledge and understanding of the participants about the importance of the 2024 Election and the use of their voting rights that will determine the future of the Indonesian nation. In addition, this PKM also provides awareness to participants of the importance of vigilance in using and dealing with social media, especially manipulative hoaxes.",